Assessing steel strains on reinforced concrete members from surface cracking patterns. (15th November 2015) - Carmo, R.N.F.; Valença, J.; Silva, D.; Dias-da-Costa, D.
Highlights: Method to assess steel strains inside concrete members using surface measurements. This approach has non-contact and does not interfere with the bond between steel and concrete. Validation using concrete ties monitored using strain gauges placed inside the steel bars. The technique can be applied to narrow regions, surrounding a single crack, or to larger regions. Results proved the feasibility of the method. Abstract: The measurement of steel strains in reinforced concrete structures is often critical to characterise the stresses along the member. In this scope, this manuscript describes the development of a method to assess steel strains inside concrete members using solely surface measurements. These measurements were obtained using photogrammetry and image processing. The technique was validated using two concrete ties monitored with strain gauges placed inside the steel bars. The experimental results showed that one of the most important parameters affecting the accuracy of the technique is the measurement of crack widths. In comparison, the concrete strain has little effect on the final results. The technique is particularly advantageous since it is non-contact and does not impact on the bond conditions. It also does not require accessing the reinforcements. As a main conclusion, this work showed the feasibility of estimating strains inside the structure using surface measurements. This technique will benefit in the near future from further improvements namely in what concerns the camera resolution.